Height, weight, weight change and risk of breast cancer in Rio de Janeiro, Brazil - Vasconcelos, Anelise Bezerra de; Mendonça, Gulnar Azevedo e Silva; Sichieri, Rosely (São Paulo Medical Journal, 2001)
CONTEXT: The relationship between body size and breast cancer still remains controversial in considering menopausal status. OBJECTIVE: To evaluate the association of height, weight and weight changes with breast cancer in the city of Rio de Janeiro, Brazil. DESIGN: Case-control study. SETTING: National Cancer Institute (INCA), Rio de Janeiro, Brazil, and State University of Rio de Janeiro (UERJ). SAMPLE: 177 incident cases of invasive breast cancer admitted to the main hospital of INCA between May 1995 and February 1996, and 377 controls recruited from among female visitors to the same hospital. MAIN MEASUREMENTS: Height and weight were measured and information on maximum weight, weight at ages 18 and 30 years, and potential risk factors were ascertained by interview at the hospital. RESULTS: Height was not related to risk of breast cancer among both pre and postmenopausal women. Nevertheless, women in this study were shorter than in studies that have found a positive association. Premenopausal women in the upper quartile of recent body mass index (BMI) and maximum BMI showed a reduced risk of breast cancer (P for trend ≤ 0.03). Weight loss between ages 18 and 30 years and from 18 years to present was also associated with breast cancer among premenopausal women. CONCLUSIONS: These findings may merely indicate the known association between leanness and breast cancer. Further studies should explore the role of weight loss on breast cancer risk.